Bubbles or cycles? Housing price dynamics in China’s major cities - Li, Jing; Wei, Yigang; Chiang, Yat Hung (International Journal of Strategic Property Management, 2020)
Based on the monthly data of 35 cities during the period 2006−2017, this study adopts a recursive forward looking method to detect the presence of housing bubbles and investigate their potential cyclical patterns in China’s large and medium sized cities. Empirical results show that the number of cities reporting housing bubbles has been increasing since 2013, before it declined in 2017. Regarding regional disparities of housing bubbles, 1st-tier and 1.5-tier cities have higher probability than 2nd-tier cities for housing bubbles. In general, eastern region cities have more housing bubbles than central and western region cities, which may indicate the problem of shrinking cities China is facing nowadays. Bubble signals for market correction in major cities and municipalities seemed alarming in particular for the period 2013−2016, however it is difficult to conclude if the market adjustment in 2017 indicates a cyclical pattern. First published online 19 December 2019